Tissue Localization and Distribution of As and Al in the Halophyte Tamarix gallica under Controlled Conditions - Sghaier, Dhouha Belhaj; Pedro, Sílvia; Diniz, Mário Sousa; Duarte, Bernardo; Caçador, Isabel; Sleimi, Noomene (Frontiers in Marine Science, 2016)
Information on localization of Al and As in Tamarix gallica is required in order to better understand the detoxification mechanisms that confer tolerance in this halophyte plant species. Plants were subjected to different Al and As concentrations with and without salt supplementation. High concentrations of As and Al have been found in Tamarix gallica leaves and roots without symptoms of toxicity to the plant, which may be related to the particular compartmentation. A sequential extraction was carried out on leaves and roots to determine and compare the metal compartmentation in the plant. In this study, subcellular localization of As and Al was determined for the first time in roots and leaves of T. gallica, and provided evidence of the detoxification mechanisms of high As and Al concentrations. These results suggest that the subcellular distribution of As and Al play important roles in avoidance of metal toxicity. The most part of Al (that has high toxicity to the plant when available forms are present) was immobilized in cell walls, potentially suppressing its transportation to other subcellular compartments more susceptible to Al toxicity. On the other hand, the greater sequestration of As in the vacuole reduces its toxicity to the remaining cell organelles in the roots, but cell wall confinement remains an important tolerant mechanism in the leaves.